A química dos chás: uma temática para o ensino de química orgânica - Silva, Denise da (2011)
This research presents a study concerning the (re) construction of the knowledge of organic chemistry by students in the 3rd stage of Education for Young and Adults (EJA) from a public school. In the search for a meaningful learning it was used the theme The chemistry of teas associated to the teaching methodology Learning Unit (UA), for having structural basis in the previous knowledge and the daily life of the students. In the development of the activities, it was offered to the students an environment favorable for the interaction and socialization of their knowledge through different activities. The data were collected through a questionnaire which aimed to know their previous conceptions; the diagnostic questionnaires which allowed to evaluate the apprenticeship of the concepts of Organic Chemistry seen in theoretical and practical forms by the theme proposed; the class casebook which allowed to testify the process of evolution of the knowledge in the different activities proposed and the final questionnaire which allowed to evaluate the proposal developed. The data were analyzed in an interpretative manner, in a predominantly qualitative approach. Based on these data, it was possible to identify the development and maturation of the knowledge of the students about organic chemistry and especially about these concepts with everyday life.